Selective delivery of remarkably high levels of gadolinium to tumour cells using an arsonium salt. Issue 70 (12th August 2021) - Windsor, Madeline S. A.; Busse, Madleen; Morrison, Daniel E.; Baker, Robert W.; Hill, Leila R.; Rendina, Louis M.
Abstract : A triphenylarsonium targeting vector is far superior to the well-established, isosteric phosphonium analogue for tumour cell delivery of Gd 3+ . Abstract : The use of a triphenylarsonium vector for tumour cell-targeting leads to a dramatic increase in Gd 3+ uptake in human glioblastoma multiforme cells by up to an order of magnitude over the isosteric triarylphosphonium analogue, with significant implications for 'theranostic' applications involving delivery of this important lanthanoid metal ion to tumour cells.